Music Composition Magringsing | Komposisi Tabuh “Magringsing” - Rama Widana Rama; Wardizal - (Pusat Penerbitan LPPMPP ISI Denpasar, 2021)
Magringsing is a music composition that is inspired by the process of making gringsing woven fabric in Tenganan Pegringsingan Village. At the stage of making gringsing fabric, there is a technique that is quite unique and rarely used in other types of woven fabrics, namely using the double ikat technique with weft and warp threads woven between each other in a vertical and horizontal manner so as to produce a unified motif. Motifs that are intact, attractive and have aesthetic value. Music composition Magringsing was the notion that rests to the patterns already existing tradition in the works that have been created previously by the development of elements of musicality poured into gamelan Semar Pegulingan Saih Pitu. The creation method used in realizing music composition Magringsing work is the Panca Sthiti Ngawi Sani method which includes the inspiration stage (ngawirasa), exploration stage (ngawacak), conception stage (ngarencana), execution stage (ngawangun) and production stage (ngebah). Music composition Magringsing work consists of four parts, and the overall duration of the work is 11 minutes. Through music composition Magringsing work, it is hoped that it can increase people's interest to love and appreciate local Balinese products which are full of philosophy, and of course have the value of beauty and privileges such as gringsing cloth. Keyword: Magringsing, double ikat, Panca Sthiti Ngawi Sani